SEROEPlDEMIOLOGY OF HELICOBACTER PYLORl - A. ÖZDEN,; Ş. DUMLU,; Ö. DÖNDERİCİ,; H. ÇETİNKAYA,; K. SOYLU,; H. ÖZKAN,; M. BALCI,; M. SARIOĞLU,; Ö. UZUNALİMOĞLU, (Turkish Journal of Gastroenterology, 2020)
-